Teacher Creativity Management In Improving The Quality Of Mathematics Learning - Taufik; Hanafiah; Supyan Sauri (Yayasan Azka Hafidz Maulana, 2023)
Learning Mathematics is the mother of science, it is unfortunate that this subject is not used as a basis for developing values ​​in building real knowledge and knowledge in the school environment. This study develops Taking a Focus related to